„Exceptional” seniors in the perception of students. - Leszczyńska-Rejchert, Anna Maria (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The elderly are often seen through the prism of negative stereotypes of old age. To change little perspective of looking at this age group, the author of the article has taken up the implementation of empirical research, in order to show the different dimensions of life of seniors, which may be regarded as “exceptional” elderly. The research’ person were students of the social sciences of Uniwersytetu Warmińsko-Mazurskiego in Olsztynie, who have agreed to select and describe one old person, in their opinion exceptional and interview with the older person. Content of the article concerns to the first part of research, which sought to determine what features of exceptional seniors note the students and identify the most common of antistereotypes of old age.